ALGORITHM FOR CREATING A NETWORK GRAPH OF THE PROJECT - Abdullaev, A.; Srazhova, U.D. (SCIENCE and SOCIETY, 2026)
This article presents an algorithm for developing a network graph for designing complex tasks. The network graph teaches the main indicators of the task, the necessary work paths, and the completion time.
Keywords: top; events; numbering; time; date of occurrence; reserve; project; required path; length